Forest structure change after forest fire in peatland of Central Kalimantan. Issue 1 (1st December 2022) - Qirom, M A; Rachmanadi, D; Lestari, F; Andriani, S
Abstract: The hydrological system of tropical peatland has been changed due to drainage. The condition caused prone to peatland burning. Forest fire affected the vegetation composition in peatland. Repeated fire causes more severe impact on vegetation and the change the peatland characteristics. The aim of the study is to obtain species composition on peatland after fire in Central Kalimantan. The research was conducted on several plots of vegetation observation on peatland that burned in 2015 (three years after fire and forth fire frequency). The plot sizes were depending on vegetation stage (seedling, sapling, poles, and trees) of 2 Ha or 50 observation plots. The measurements of parameter were species, density, frequency, and important value index. The species composition was described by ecological indices such as Shannon wiener index, Simpson index, and evenness index. The results showed that species diversity and ecological index were very low. That condition indicated that the fire has changed the species composition and the natural regeneration has been obstructed. Combretocarpus Rotundatus and Cratoxylon glaucum were presented on overall tree stage as pioneer species, but the climax species didn't found on three years after forest fire. Based on the results, the repeated fires caused an extreme decrease of natural regeneration so the ability of recovery is not running well. The parameters can be used in determining the priority of revegetation program on large scale.